2018
DOI: 10.18203/2394-6040.ijcmph20180949
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess awareness on disaster management among school going children in Gwalior (M.P.)

Abstract: INTRODUCTION"Disaster, by Oxford dictionary's simple definition is an unexpected event, that kills a lot of people or causes huge damage". 1 The Centre for Research on the Epidemiology of Disaster (CRED) in Brussels, Belgium has come up with a modified definition i.e., "A disaster is a situation or event which overwhelms local capacity, necessitating a request to a national or international level of external assistance".2 As per CRED an event can be classified as a disaster if, it kills more than 10 people/im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
(2 reference statements)
0
4
0
Order By: Relevance
“…Meanwhile the percent of them who had satisfactory knowledge significantly increased to 61% after the educational program implementation, which proved statistically (22) . Also, In the same line, Marskole B in 2018, Mhaske in 2012 and Suresh in 2010 found that, the teaching program succeeded in achieving significant improvements among study subjects" knowledge regarding disaster management (23,24,25) .…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile the percent of them who had satisfactory knowledge significantly increased to 61% after the educational program implementation, which proved statistically (22) . Also, In the same line, Marskole B in 2018, Mhaske in 2012 and Suresh in 2010 found that, the teaching program succeeded in achieving significant improvements among study subjects" knowledge regarding disaster management (23,24,25) .…”
Section: Discussionmentioning
confidence: 89%
“…However, their effect can be mitigated. Disaster management effort aim to reduce or avoid potential losses from hazards, so we can assure correct or appropriate help to victims of disaster and achieve rapid recovery [5].…”
Section: Need For the Studymentioning
confidence: 99%
“…The linkage of knowledge of disaster mitigation with children at the elementary school level is described (Sari et al, 2014) to build a culture of security and resilience in the face of disasters. Students are able to act quickly, precisely and accurately when facing disasters (Desfandi, 2014), from the knowledge they have can help people to save themselves and their groups in the future (Marskole et al, 2018). Increasing in-depth and comprehensive knowledge about natural disasters (Atmojo et al, 2018), reducing the risk of material and immaterial community groups (Winarmi & Purwandi, 2018).…”
Section: Introductionmentioning
confidence: 99%